2016
DOI: 10.1246/bcsj.20150407
|View full text |Cite
|
Sign up to set email alerts
|

Scope and Limitations of Supramolecular Autoregulation

Abstract: Recently, our group has reported on the ureidopyrimidinone (UPy) induced buffering of 2,7-diamido-1,8-naphthyridine (NaPy) and used this phenomenon to regulate the catalysis of the Michael addition of 2,4-pentanedione to trans-β-nitrostyrene. We now show that the observed catalytic activity of NaPy is the result of a strong synergy between NaPy and trace amounts of K 2 CO 3 , resulting in a more than 100-fold increase in reaction rate compared to the two compounds separately. By keeping the concentration of K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…In good agreement with our previous work on a structurally similar NaPy,26 both NaPy 1 and K 2 CO 3 were found to be required for efficient catalysis between Mal ref 3 and Pent ref 4 (Fig. 2a and b).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In good agreement with our previous work on a structurally similar NaPy,26 both NaPy 1 and K 2 CO 3 were found to be required for efficient catalysis between Mal ref 3 and Pent ref 4 (Fig. 2a and b).…”
Section: Resultssupporting
confidence: 92%
“…1a). 26 It was shown that this reaction displays bimolecular reaction kinetics and that the overall reaction rate can be regulated by inhibition using the NaPy complementary ureidopyrimidinone (UPy) motif 26. We also showed that a fixed ratio of NaPy and ditopic UPy can be diluted while buffering the concentration of catalytically active free NaPy, thereby desensitizing the Michael additions' rate to dilution 2427…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequent investigations have shown that the catalytic activity of NaPy 2 is more complex than previously reported and that it most probably acts as a buffered phase transfer catalyst. 16 Here, we focus on the observation that the concentration of free NaPy (C NaPyfree ) can be buffered over a large concentration range when the concentrations of both NaPy (C NaPy-total ) and ditopic UPy (C ditopic UPy ) are increased simultaneously in a 1:1 ratio. The molecular mechanism by which component buffering occurs is described by a two-component equilibrium model that describes competition between cyclization and chain growth of a ditopic molecule and end-capping by a monotopic component.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported on a two-component supramolecular buffering system based on a self-associating divalent ureidopyrimidinone (UPy) molecule and a monovalent naphthyridine (NaPy) molecule that undergoes dimerization with UPy chain ends ( 29 , 30 ) ( Fig. 1 A ).…”
mentioning
confidence: 99%